Будівельно-інжинірингові фірми – суб’єкти управління інвестиційними ресурсами будівельних проектів - Тугай, О. А.; Орищенко, В. В. (Ways to Improve Construction Efficiency, 2014)
Methodological basis of planning of organizational structures is certain for building-engineering firms taking into account their leading role in a management by the resources of investor at building of building objects. The structures created on the basis of offered approach provide organizationally is a technological design and resource-calendar planning of processes of building of building objects on alternative basis, legal accompaniment of project, rational co-operating with the central and local organs of supervision, operative management by building projects on by the observance of their pre-arranged parameters and concordance of interests and actions of all organizations-participants.